Smooth muscle cells-specific loss of OCT4 accelerates neointima formation after acute vascular injury - Shin, Junchul; Tkachenko, Svyatoslav; Gomez, Delphine; Tripathi, Rupande; Owens, Gary K.; Cherepanova, Olga A. (Frontiers in Cardiovascular Medicine, 2023)
There is growing evidence that smooth muscle cell (SMC) phenotypic transitions play critical roles during normal developmental and tissue recovery processes and in pathological conditions such as atherosclerosis. However, the molecular mechanisms responsible for these transitions are not well understood. Recently, we found that the embryonic stem cell/induced pluripotent stem cell (iPSC) factor OCT4, which was believed to be silenced in somatic cells, plays an atheroprotective role in SMC, and regulates angiogenesis after corneal alkali burn and hindlimb ischemia by mediating microvascular SMC and pericyte migration. However, the kinetics of OCT4 activation in arterial SMC and its role in acute pathological conditions are still unknown.Here, using an Oct4-IRES-GFP reporter mouse model, we found that OCT4 is reactivated in the carotid artery 18 hours post-acute ligation-induced injury, a common in vivo model of the SMC phenotypic transitions. Next, using a tamoxifen-inducible Myh11-CreERT2 Oct4 knockout mouse model, we found that the loss of OCT4, specifically in SMC, led to accelerated neointima formation and increased tunica media following carotid artery ligation, at least in part by increasing SMC proliferation within the media. Bulk RNA sequencing analysis on the cultured SMC revealed significant downregulation of the SMC contractile markers and dysregulation of the genes belonging to the regulation of cell proliferation and, positive and negative regulation for cell migration ontological groups following genetic inactivation of Oct4. We also found that loss of Oct4 resulted in suppression of contractile SMC markers after the injury and in cultured aortic SMC. Further mechanistic studies revealed that OCT4 regulates SMC contractile genes, ACTA2 and TAGLN, at least in part by direct binding to the promoters of these genes.These results demonstrate that the pluripotency factor OCT4 is quickly activated in SMC after the acute vascular injury and inhibits SMC hyperproliferation, which may be protective in preventing excessive neointima formation.